2008
DOI: 10.1098/rspb.2008.0517
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific responses to vocal convergence and divergence of contact calls in orange-fronted conures (Aratinga canicularis)

Abstract: We investigated the signal function of vocal imitation of contact calls in orange-fronted conures (OFCs; Aratinga canicularis) in Costa Rica. OFCs live in dynamic social systems with frequent flock fusions and fissions. Exchanges of contact calls precede these flock changes. During call exchanges, the similarity between the contact calls of different individuals may either increase (converge) or decrease (diverge). We conducted a playback experiment on wild-caught captive birds in which we simulated convergent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…There does, however, appear to be a differential response by sex whereby males preferentially reply to convergent 'chee' calls and females reply to both convergent and divergent calls (Balsby & Scarl, 2008). The fact that both sexes respond to convergent calls in a nonagonistic context suggests it has an affiliative function (Balsby & Scarl, 2008) that may facilitate the addressing of individuals (Balsby et al, 2012). There are also more subtle forms of vocal matching, with some primate species matching fine-scale features of a call type when calling together as a means of social affiliation (Mitani & Brandt, 1994;Sugiura, 1998) or to promote partner preferences (Biben et al, 1986).…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…There does, however, appear to be a differential response by sex whereby males preferentially reply to convergent 'chee' calls and females reply to both convergent and divergent calls (Balsby & Scarl, 2008). The fact that both sexes respond to convergent calls in a nonagonistic context suggests it has an affiliative function (Balsby & Scarl, 2008) that may facilitate the addressing of individuals (Balsby et al, 2012). There are also more subtle forms of vocal matching, with some primate species matching fine-scale features of a call type when calling together as a means of social affiliation (Mitani & Brandt, 1994;Sugiura, 1998) or to promote partner preferences (Biben et al, 1986).…”
Section: Discussionmentioning
confidence: 74%
“…Instead, convergent, divergent and variable patterns of call type similarity are observed in response to 'chee' call playbacks (Balsby & Bradbury, 2009). There does, however, appear to be a differential response by sex whereby males preferentially reply to convergent 'chee' calls and females reply to both convergent and divergent calls (Balsby & Scarl, 2008). The fact that both sexes respond to convergent calls in a nonagonistic context suggests it has an affiliative function (Balsby & Scarl, 2008) that may facilitate the addressing of individuals (Balsby et al, 2012).…”
Section: Discussionmentioning
confidence: 91%
“…However, this does not necessarily mean that crows are insensitive to sex in their communications. Previous studies in birds revealed that social interactions differed depending on sex combinationsfor example, higher aggression between males in largebilled crows, as well as other corvids [12,13,21], and strong responses to contact calls of opposite-sex individuals in orange-fronted conures (Aratinga canicularis) [22]. These sex effects on social interactions suggest that responses of subjects to the played-back calls might be influenced by the combination of the stimulus and the subject sexes.…”
Section: Discussionmentioning
confidence: 99%
“…These birds may simply need greater motivation in order to be able to vocalize what they heard in spite of instances that they can readily mimic even instrumental sounds or artificial noises occasionally (Gramza, 1970). Several playback experiments in other two parrot species (Balsby & Scarl, 2008;Scarl & Bradbury, 2009;Vehrencamp et al, 2003) suggests that not only direct social interaction but other contexts such as like a territorial protection, may also play an important role for vocal imitation. Perhaps constructing some of these more "natural contexts" in the experimental domain may be able to identify the key components that facilitate vocal imitation in budgerigars.…”
Section: Importance Of Social Interaction and Contextsmentioning
confidence: 99%